Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (New York University Press, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Section: vii, 274 p. ; 24 cm.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

Re-orienting desire: The gay international and the arab world - Massad, Joseph (Public Culture, 2002)
Keywords: approches et analyses; cours; discours dominant; fem3400; identités LGBTQIA2+; islam; premier cycle; racisme; ressource en ligne; sexualité; système colonial; systèmes d'oppressions; thématiques; violences